Does team-based learning develop essential generic skills in pharmacy students? - Eksteen, M.J. (South African Journal of Higher Education, 2019)
In order to deliver graduates with the necessary qualities, skills and understanding to be employable, universities should do more than only teach disciplinary content. TBL is a small-group-based, active learning teaching strategy which supports the development of essential skills while mastering course content. In this study, a questionnaire was used to collect biographical data. It consisted of 20 quantitative questions focusing on essential generic skills developed during the implementation of TBL in a fourth-year pharmacy course. Participation was voluntary and ethical approval was received from the faculty’s ethics committee. The results pointed out that pharmacy students developed essential generic skills such as teamwork, problem-solving, interpersonal skills, time management, communication and adaptability when TBL was used as teaching strategy. TBL does not discriminate against age, gender or ethnicity, which makes it a valuable teaching strategy in South African higher education settings.